2021
DOI: 10.1175/jpo-d-20-0103.1
|View full text |Cite
|
Sign up to set email alerts
|

Convection and Heat Transfer in Island (Warm) Wakes

Abstract: The interaction between the incoming winds with high mountainous islands produces a wind-sheltered area in the leeward side, known as the atmospheric wake. In addition to weaker winds, the wake is also characterized by a clearing of clouds, resulting in intense solar radiation reaching the sea surface. As a consequence, a warm oceanic wake forms on the leeward side. This phenomenon detectable from space can extend 100 km offshore of Madeira, where the sea surface temperature can be 4⁰C higher than the surround… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…The accuracy of the modeled surface wind was also assessed at three specific locations (points 1, 2, and 3 represented in Figure 3B), and are presented in Table 2 for both descending and ascending satellite passages. Points 1 and 3 are located close to the regions of the atmospheric jets (Alves et al, 2020(Alves et al, , 2021, and point 2 is in the southern region characterized by the frequent occurrence of warm wakes (Caldeira et al, 2002(Caldeira et al, , 2016Couvelard et al, 2012;Grubišic et al, 2015;Azevedo et al, 2021). In general, correlation coefficients were high (0.78-0.96) and RMSE values were low (mostly < 1.6 m s −1 ; Table 2), showing the strong performance of the model with respect to representing the wind variability.…”
Section: Atmospheric Model Validationmentioning
confidence: 93%
See 2 more Smart Citations
“…The accuracy of the modeled surface wind was also assessed at three specific locations (points 1, 2, and 3 represented in Figure 3B), and are presented in Table 2 for both descending and ascending satellite passages. Points 1 and 3 are located close to the regions of the atmospheric jets (Alves et al, 2020(Alves et al, , 2021, and point 2 is in the southern region characterized by the frequent occurrence of warm wakes (Caldeira et al, 2002(Caldeira et al, , 2016Couvelard et al, 2012;Grubišic et al, 2015;Azevedo et al, 2021). In general, correlation coefficients were high (0.78-0.96) and RMSE values were low (mostly < 1.6 m s −1 ; Table 2), showing the strong performance of the model with respect to representing the wind variability.…”
Section: Atmospheric Model Validationmentioning
confidence: 93%
“…Previous studies in this region focused on atmospheric and oceanic island processes, combining the use of mediumhigh resolution numerical models (Caldeira and Sangrà, 2012;Couvelard et al, 2012;Caldeira and Tomé, 2013;Nunalee and Basu, 2014;Pullen et al, 2017b;Alves et al, 2021;Miranda et al, 2021), with in situ and satellite data (Caldeira et al, 2001(Caldeira et al, , 2002(Caldeira et al, , 2014Grubišic et al, 2015;Alves et al, 2020;Azevedo et al, 2021). These studies revealed the complexity and variety of oceanic and atmospheric interactive processes which occur around the Data was estimated based on the drainage network computed from the Digital Terrain Model (described in section "MOHID-Land, the Hydrological Model") using QGIS version 3.14.1 (www.qgis.org).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a high mountain ridge (ca. 1800 m) in the island's interior obstructs the dominant northeast trade winds, leading to warmer and sheltered waters in the south of Madeira (Caldeira et al, 2002;Caldeira and Sangrà, 2012;Azevedo et al, 2021).…”
Section: Study Areamentioning
confidence: 99%
“…Their study highlights the necessity of considering heterogeneous atmospheres (especially in the presence of vortex streets) for optical wave propagation studies. With a focus on atmosphere-ocean interactions, Azevedo et al (2020) studied the detailed responses of upper oceanic profiles of temperature, salinity, and turbulence to the Madeira warm wakes, which mainly result from intense solar radiation in cloud-free conditions.…”
Section: Introductionmentioning
confidence: 99%